Change in value-relevance of disclosed RPT across accounting regimes: Evidence from Malaysia - Maigoshi, Zaharaddeen Salisu; Abdul Latif, Rohaida; Kamardin, Hasnah (Elsevier B.V., 2017)
This study investigates the value-relevance of the disclosure of the related party transaction and whether the value-relevance of such disclosure has changed after the mandatory adoption of international financial reporting standard (IFRS) in 2012 by listed firms in Malaysia.Analyses of the sampled firm from 2009 to 2015 revealed that the disclosure of related party transaction is value-relevant. We also find that earnings per share are value-relevant in pre-IFRS adoption, post-IFRS adoption and combined periods, while book value per share is only value-relevant in the post-IFRS adoption and combined periods.Our results also recorded a significant decrease in the value-relevance of the book value per shares of the firms with related party transactions during the post-IFRS adoption and combined periods. Conversely, the value-relevant of earnings per share of the firms with related party transaction increased in the post-IFRS adoption and combined periods. Our results are robust to the number of tests to validate our results.